(untitled) (Global Journal of Medical Research, 2024)
Systemic Arterial Hypertension SAH is the most important risk factor for the development of cardiovascular diseases being one of the most prevalent diseases worldwide Tobacco use has been linked with the development of systemic arterial hypertension or with a difficult control of it However it has not yet been universally accepted or demonstrated whether this relationship is directly proportional to vascular damage in people who consume it The purpose of the study is to compare the effect of smoking on hypertensive smokers vs nonsmoking hypertensive patients